The antimicrobial peptide LL‐37 induces synthesis and release of cysteinyl leukotrienes from human eosinophils – implications for asthma. Issue 3 (18th January 2013) - Sun, J.; Dahlén, B.; Agerberth, B.; Haeggström, J. Z.
Abstract: Background: Eosinophils and their products, including leukotrienes and eosinophil cationic protein (ECP), are well‐known mediators of inflammation and tissue damage in asthma. The antimicrobial peptide LL‐37 exhibits a variety of immunomodulatory activities. However, the role of LL‐37 in asthma has not been fully addressed. Here, we aim to investigate the effect of LL‐37 on inducing inflammatory mediators in human eosinophils, probe the underlying mechanisms, and search for a clinical correlate. Methods: Primary eosinophils were isolated from peripheral blood. Leukotriene and ECP levels were measured using EIAs or ELISAs. Activation of leukotriene‐synthesizing enzymes and signaling kinases was analyzed by Western blot or immunofluorescent imaging. LL‐37/its proform hCAP18 expression was analyzed by Western blot. Results: LL‐37, via formyl peptide receptor‐2 (FPR‐2), triggered the release of cysteinyl leukotrienes (cys‐LTs) from eosinophils. The release was more prominent in cells primed with the eosinophilopoietic cytokine GM‐CSF or IL‐5 or cells from asthmatic patients. LL‐37 stimulates lipid body formation and activates cys‐LT‐synthesizing enzymes by multiple mechanisms: enhancing cPLA2 activity by pERK1/2‐mediated phosphorylation and inducing intracellular translocation and assembly of 5‐LO and LTC4 S at perinuclear locations and lipid bodies. In addition to cys‐LTs, LL‐37 enhances ECP release from eosinophils via pERK1/2. The expression of hCAP18 and its release following leukotriene stimulation are significantly higher in eosinophils from asthmatics. Conclusions: This study identifies LL‐37 as an eosinophil‐activating peptide that triggers release of inflammatory mediators. The clinical correlation suggests that LL‐37/hCAP18 and its signaling pathway represent potential therapeutic targets for this disease.